2018
DOI: 10.1021/acs.chemmater.7b04860
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Mesostructured Silica Nanoparticles into Colloidal Hollow Nanoparticles in the Presence of a Bridged-Organosiloxane Shell

Abstract: Hollow siloxane-based nanoparticles (HSNs) have attracted significant attention because of their unique properties and applications. Recently, it was discovered that the simple covering of silica nanoparticles with an organosiloxane shell leads to the spontaneous formation of HSNs; however, the detailed mechanism of their formation has not yet been established. In this study, colloidal 30 nm HSNs were prepared by adding organically bridged alkoxysilane to an aqueous dispersion of mesostructured silica–surfacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 49 publications
5
22
0
Order By: Relevance
“…In order to generalize the process and to control the hollow structures, Kuroda and co‐workers have systemically investigated the mechanism for the transformation of SiO 2 hard cores into HPMO nanospheres via the deposition of a organosilica shell . They have demonstrated that the soluble silicates of the SiO 2 hard‐core suspensions slightly decreased after the structural transformation.…”
Section: Synthesismentioning
confidence: 99%
“…In order to generalize the process and to control the hollow structures, Kuroda and co‐workers have systemically investigated the mechanism for the transformation of SiO 2 hard cores into HPMO nanospheres via the deposition of a organosilica shell . They have demonstrated that the soluble silicates of the SiO 2 hard‐core suspensions slightly decreased after the structural transformation.…”
Section: Synthesismentioning
confidence: 99%
“…[58][59][60] In particular, the control over surfactant/silica assembly realizes the construction of various types of porous structures, which have been well studied via ET. [58][59][60] In particular, the control over surfactant/silica assembly realizes the construction of various types of porous structures, which have been well studied via ET.…”
Section: Silica Hollow Spheresmentioning
confidence: 99%
“…Compared to carbon hollow spheres, silica nanoparticles have been engineered with more complicated structures due to the ease of structure tailoring via various synthesis strategies. [58][59][60] In particular, the control over surfactant/silica assembly realizes the construction of various types of porous structures, which have been well studied via ET. [61][62][63] The hollow intervals are typically distinguished by the highcontrast edge of silica shell using conventional TEM.…”
Section: Silica Hollow Spheresmentioning
confidence: 99%
“…For instance, immobilizing enzymes on silica needs this hybridization. However, many methods of enzyme immobilization rely on cross-linking and covalent immobilization [19]. In most cases, these methods deal with drawbacks such as inactivation of the enzyme by occupying the active sites of the enzyme and affecting the rotational mobility [20] or increasing the steps of preparation which make the process unsuitable for an efficient (photo)(bio)catalytic process.…”
Section: Introductionmentioning
confidence: 99%